Penggunaan Media Audio Visual untuk Meningkatkan Keterampilan Menyimak Dongeng Pelajaran Bahasa Indonesia - Widiastuti Widiastuti (Publikasi Indonesia, 2023)
This research was motivated by the learning conditions of Indonesian, especially in class VI of SD Negeri 24 Pallimae with the subject matter of fairy tale listening skills. So the evaluation value is low. This is because teachers only use practice methods and do not use media in learning. The method used in this study is Class Action Research. Research is carried out in two cycles, one cycle consists of learning planning, learning implementation process, observation and reflection activities. The researcher took the research subject of grade VI students of SD Negeri 24 Pallimae, Poleang District, Bombana Regency with a total of 20 students. The results showed that in the implementation of the end of cycle 1, out of 20 class VI students, an average score of 34.6 from a total score of 60 or reaching 57.7% was obtained, then at the end of the 2nd cycle, from 20 class VI students, an average score of 44.1 was obtained from a total score of 60 or reached 73.5%. This research has proven that the use of audio-visual media can increase students' understanding of the content of fairy tales in Indonesian lessons in class VI of SD Negeri 24 Pallimae, Poleang District, Bombana Regency, Academic Year 2021/2022.